Coherent detection-based photonic radar for autonomous vehicles under diverse weather conditions. - Sushank Chaudhary; Lunchakorn Wuttisittikulkij; Muhammad Saadi; Abhishek Sharma; Sattam Al Otaibi; Jamel Nebhen; Demostenes Zegarra Rodriguez; Santosh Kumar; Vishal Sharma; Gridsada Phanomchoeng; Ratchatin Chancharoen (PLoS ONE, 2021)
Autonomous vehicles are regarded as future transport mechanisms that drive the vehicles without the need of drivers. The photonic-based radar technology is a promising candidate for delivering attractive applications to autonomous vehicles such as self-parking assistance, navigation, recognition of traffic environment, etc. Alternatively, microwave radars are not able to meet the demand of next-generation autonomous vehicles due to its limited bandwidth availability. Moreover, the performance of microwave radars is limited by atmospheric fluctuation which causes severe attenuation at higher frequencies. In this work, we have developed coherent-based frequency-modulated photonic radar to detect target locations with longer distance. Furthermore, the performance of the proposed photonic radar is investigated under the impact of various atmospheric weather conditions, particularly fog and rain. The reported results show the achievement of significant signal to noise ratio (SNR) and received power of reflected echoes from the target for the proposed photonic radar under the influence of bad weather conditions. Moreover, a conventional radar is designed to establish the effectiveness of the proposed photonic radar by considering similar parameters such as frequency and sweep time.